2016
DOI: 10.5935/1678-9741.20160066
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial Approach Provides Better Outcomes in the Surgical Treatment of Cardiac Myxomas

Abstract: ObjectiveWe aimed to present clinical features, surgical approaches, importance of surgical technique and long-term outcomes of our patients with cardiac myxoma who underwent surgery.MethodsWe retrospectively collected data of patients with cardiac myxoma who underwent surgical resection between February 1990 and November 2014. Biatrial approach is the preferred surgical method in a large proportion of patients that are operated due to left atrial myxoma because it provides wider exposure than the uniatrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
(50 reference statements)
2
17
0
1
Order By: Relevance
“…Microscopically, myxoma is generally a hypocellular lesion with the prominent myxoid stromal background. The neoplastic cells are frequently stellate, or spindle in shape and tend to arrange singly or less frequently in small cords or nests and intramural hemorrhage and calcification were occasionally present [4]. In our series, the histopathological diagnosis was confirmed in all patients.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Microscopically, myxoma is generally a hypocellular lesion with the prominent myxoid stromal background. The neoplastic cells are frequently stellate, or spindle in shape and tend to arrange singly or less frequently in small cords or nests and intramural hemorrhage and calcification were occasionally present [4]. In our series, the histopathological diagnosis was confirmed in all patients.…”
Section: Discussionsupporting
confidence: 60%
“…None of the patients in our study expressed familial inheritance. Cardiac myxoma may arise from the left atrium, right atrium, the atrioventricular valves, the ventricles, or may rarely originate from the ventricular free wall or atrial appendages [4], All the published series in the literature showed that the left atrium is the most common site of myxoma, with the tumor base on the inter-atrial septum in 80% of the cases. [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yüksel et al 16 presented a retrospective study, which compared biatrial approach (n=34) with unilateral approach (n=8) and right atriotomy and right ventriculotomy (n=1) in patients with LA myxoma. They preferred biatrial approach for wide resection of the tumour and to avoid residual tumour.…”
Section: Discussionmentioning
confidence: 99%